Pentingkah Pekerjaan Ibu dalam Literasi Anak di Indonesia? - Nur Asrofi, Dien Amalina; Al Ayyubi, Muhammad Salahudin (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
This study aims to analyze the impact of maternal employment status and job type on children's literacy skills in Indonesia, using data from the 2023 National Socioeconomic Survey (SUSENAS) and a binary logistic regression approach. The results show that working mothers, particularly those in the formal sector, are positively and significantly correlated with children's literacy, especially in non-poor households. These findings highlight the important role of maternal employment contribution in strengthening educational investment within families. In contrast, among poor households, formal employment of mothers does not significantly influence children's literacy, indicating that economic constraints remain a major barrier. In addition, child-specific factors such as gender, household economic status, and geographic location, also affect literacy outcomes; girls, children from non-poor households, and those living in Java tend to have higher literacy levels. The policy implications suggest the need to promote maternal economic empowerment by expanding inclusive access to employment through skills training, flexible job opportunities, and entrepreneurial support tailored to the needs of women as primary caregivers. Furthermore, gender-responsive educational interventions and strengthened educational support for poor households and underdeveloped regions are crucial to ensure equitable and inclusive literacy development nationwide.